Knowledge and practice of nursing personnel in the prevention of mechanical ventilation associated pneumonia - Wagner Thomas Granizo-Taboada; Melany Mishell Jiménez-Jiménez; Jorge Luis Rodríguez-Díaz; Melynn Parcon-Bitanga (Archivo Médico de Camagüey, 2020)
Background: ventilator associated pneumonia represents one of the major problems in the intensive care unit due to the fact that it aggravates the patient's clinical condition, prolongs hospital stay and increases the cost of hospitalization. As infection is preventable and healthcare related, its control is mainly attributed to the nursing staff. Objective: to evaluate the knowledge and nursing practice involved in the methods of prevention of hospital acquired pneumonia in patients with mechanical ventilation. Methods: a quantitative, cross-sectional study was employed from June 1st until August 31st, 2018. A structured, observational guide and a questionnaire was applied to the population composed of 22 nursing personnel in the intensive care unit. Results: of the evaluated nurses, it was found out that they possess knowledge of both theory and practice, particularly, regarding the use of protective barriers, correct position for endotracheal aspiration and as well as the number of times the procedure should be applied. Conclusions: adequate knowledge about theory and practice exists among nurses who attended mechanically ventilated patients in critical condition. Moreover, the quantity of nursing work experience does not affect the quality of care given to the patients.